ANALISA PENGUKURAN EFEKTIVITAS MESIN PADA PROSES FILLING MENGGUNAKAN METODE OVERALL EQUIPMENT EFECTIVENESS (OEE) & SIX BIG LOSSES DI PT SANBE FARMA BANDUNG - Faza Millatina Taufik; Grace Natalie Puri; Mega Meidina; Rafi Muhammad Zidan (LPPM Universitas Bina Bangsa, 2023)
PT Sanbe Farma is a company in the field of pharmaceutical industries that carry out the development of formulation, production, and sales of safe and high-quality drug products. What must be considered within the company is the effectiveness of the engine work is one of the machines in the filing process that becomes the core process of a product. Productivity of a filling process can be increased/maintained by conducting routine evaluations to the process. The evaluation carried out is by the analysis of OEE (Overall Equiphyllity). OEE (Overall Equipment Effect) is a method of calculation that is used to determine the effectiveness of a process that is being carried out by identifying the percentage of truly productive production time which is influenced by three factors, namely availability, performance, and quality. The research was conducted by observing the filling process on the filling I process and collecting the data needed such as down time/time loss every day, the packaging results obtained in one day, one batch's packaging results, and other supporting data. Based on the observation results, the value of OEE was obtained in machine I filling process was 88.5% with the main losses causes are Reduced Speed and Set up Adjustment